Hepatoprotective Effect of Trigona spp. Bee Propolis against Carbon Tetrachloride-Induced Liver Injury in Rat - Rachel Amelia; Achadiyani Achadiyani; M. Begawan Bestari (Althea Medical Journal, 2016)
Background: Oxidative stress reaction can cause liver injury. This process can be prevented by antioxidant activities which can break the destructive chain caused by free radical substances in the liver. Propolis produced by Trigona spp. bee is known to have a high level of antioxidant. The aim of this study was to examine the effect of Trigona spp. bee propolis on liver histological toxicity caused by carbon tetrachloride-induced oxidative stress.Methods:This experimental study was conducted in September 2013 at the Animal Laboratory of Departement of Pharmacology and Therapy, Faculty of Medicine Universitas Padjadjaran. Twenty-four healthy male Wistar rats as objects were adapted for one week and randomly divided into 3 groups. Group I was the control negative, group II was given carbon tetrachloride on day 14, group III was given Trigona spp. bee propolis on day 1-14. On day 14, group III was injected CCl4 intraperitoneally. The quantitative data were statistically analyzed using the one way ANOVA and Tukey test with p value < 0.05.Results: Group I showed the liver contained normal cells, without significant injury of the membrane, round and complete nucleus. The average number of liver cell was 464 ± 9.59281 cells/field; group II underwent necrosis and the average of the cells was 146 ± 7.56885 cells/field; group III showed some normal liver cells, and some necrotic area with the normal liver cells average was 263 ± 14.10860 cells/field. The p-value=0.00.Conclusions: Trigona spp. bee propolis has a hepatoprotective effect against CCl4-induced liver injury histologically. [AMJ.2016;3(3):481–5]DOI: 10.15850/amj.v3n3.861